2016
DOI: 10.1111/nad.12049
|View full text |Cite
|
Sign up to set email alerts
|

The Pulse Nightclub Shooting: Connecting Militarism, Neoliberalism, and Multiculturalism to Understand Violence

Abstract: The shooting that left 49 people dead and 53 people injured at the Pulse nightclub in Orlando, Florida shined an international spotlight on the violent oppression of LGBTQ+ people. The significant loss of human life, the complex intersections of identity, and the horrific details of the crime brought numerous issues affecting the lives of LGBTQ+ people into public discourse. This essay contextualizes the narratives surrounding Pulse with a political economic analysis of the massacre, its antecedents, and its a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…In response, many gay bars in large metropolitan cities have employed neoliberal strategies to remain financially viable and culturally relevant (e.g., Hartless, 2019; Mattson, 2014). Accordingly, Kalish Blair (2016) denoted how gay bars, such as Pulse Nightclub, adopt neoliberal strategies where diverse groups are given specific nights (e.g., Latin night or lesbian night). Other strategies such as drag brunch, intended to make drag performance more accessible to heterosexual audiences, have become major sources of income (Siddons, 2019).…”
Section: Neoliberalism Branding and Gay Barsmentioning
confidence: 99%
“…In response, many gay bars in large metropolitan cities have employed neoliberal strategies to remain financially viable and culturally relevant (e.g., Hartless, 2019; Mattson, 2014). Accordingly, Kalish Blair (2016) denoted how gay bars, such as Pulse Nightclub, adopt neoliberal strategies where diverse groups are given specific nights (e.g., Latin night or lesbian night). Other strategies such as drag brunch, intended to make drag performance more accessible to heterosexual audiences, have become major sources of income (Siddons, 2019).…”
Section: Neoliberalism Branding and Gay Barsmentioning
confidence: 99%
“…According to Duggan (2003), Reagan used neoliberalism as a way to push against the former Keynesian policies, like the New Deal, to lessen the government's responsibility in social welfare programs while cutting taxes for the rich and restructuring the K-20 education system from a public to a private good. Neoliberalism seeks to uphold capitalism through interlocking systems of oppression, highlighting the ableist, classist, cis-heteronormative, and white supremacist underpinnings of our systems (Duggan, 2003;Kalish Blair, 2016;Museus & LePeau, 2019). Maher and Aquanno (2018) identified how U.S. education systems are organized and suggested that it is "not merely a state policy paradigm or corporate asset portfolio, but rather a trend in the institutional organization of power" (p. 33); this speaks to the ways hegemonic socialization impacts and effects neoliberalism within higher education institutions.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…To be sure, discussion of the USA generally appeared very little throughout the articles. During the same 911 phone call as Mateen's “pledged allegiance” statement, he repeatedly called for an end to US-initiated bombings, telling the negotiator “you need to stop the US air strikes” and “you have to tell America to stop bombing Syria and Iraq, they are killing a lot of innocent people,” among other similar statements (Brennan, 2016; Kalish Blair, 2016).…”
Section: Condemning Islamophobia and Reinforcing Homonationalismmentioning
confidence: 99%
“…On 12 June 2016, Omar Mateen, a US citizen born in New Hyde Park, New York, and living in Fort Pierce, Florida, killed 49 people in Orlando at a gay nightclub, Pulse, on “Latin night” (Kalish Blair, 2016; Koons, 2017; Lawrence, 2016). Still, as these quotations from Barack Obama and Hillary Clinton reflect, Mateen was frequently positioned in opposition to US norms, rather than a product of them, including by those on the US political left.…”
mentioning
confidence: 99%
See 1 more Smart Citation